Hungarian Monitoring, 8 September 1990 . [Magyar rádiófigyelő], 1990. szeptember 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev in Helsinki - Saddam Hussein's radio and TV address - Crimean peninsula would become autonomous republic - New election law in Albania Domestic Affairs: - Trianon memorial - Debate over the secret services - Environmental protection conference in Körmend Economy: - Hungary and the restructuring of the international mineral oil market - Used car market opens in Budapest Külpolitika: - Gorbacsov Helsinkiben - Szaddam Husszein rádió - És TV-üzenete - Autonóm köztársasággá válna a Krím-félsziget - Új választási törvény Albániában Belpolitika: - Trianoni emlékmű - Vita a titkosszolgálatokról - Környezetvédelmi tanácskozás Körmenden Gazdaság: - Magyarország és a nemzetközi kőolajpiac átrendeződése - Használtautó piac nyílik Budapesten